Learning Media Technological Competence for Teachers Using the Canva Application - Abdul Hafiz; Barsihanor Barsihanor; M Fahmi Arifin (Al-Qalam Institute, 2024)
This study aims to enhance teachers' technological competence in creating learning media using the Canva application for teachers in madrasah ibtidaiyah, emphasizing its role in improving the quality of teaching and student engagement. The study highlights the increasing demand for interactive and visually appealing educational content in modern teaching environments, necessitating teachers' proficiency in utilizing technology-based tools. The research employed a qualitative approach with data gathered through interviews, observations, and documentation. The methods included participatory action research to provide teachers with hands-on experience mastering Canva. Key activities involved lectures, practical workshops, and collaborative evaluations, enabling participants to develop skills systematically. Findings revealed significant improvements in teachers' abilities to design engaging and visually compelling educational content. Interviews indicated increased enthusiasm and confidence among teachers, while observations demonstrated a positive learning curve in mastering Canvas features. Documentation highlighted learning materials' enhanced quality and interactivity, leading to higher student motivation and participation. These findings contribute to the broader discourse on integrating technology in education, showcasing Canva's potential as an accessible tool for empowering teachers and enhancing the learning experience.